Abu Ishak al-Thalabi’s “The Lives of the Prophets” as a Source of “The Embassy of Isa to Antioch” Attested in Lithuanian Tatars’ Kitabs - Temchin, Sergey (Slavistica Vilnensis, 2019)
The author argues that the Ruthenian text known as The Embassy of Isa to Antioch and written using the Arabic script in manuscript kitabs produced by the Tatars of the Grand Duchy of Lithuania is an abbreviated version of a chapter from the Lives of the Prophets by Abu Ishak Ahmad ibn Muhammad al-Thalabi (died 1035), the famous Sunni Islam theologian, historian, and mufassir who worked in Nishapur (Northeastern Iran). The Ruthenian text is reproduced in a Latin transliteration alongside the English translation of the corresponding chapter of the Arabic treatise.